Banco Comercial Português : equity valuation - Pessanha, João Miguel Magalhães da Silva (2014)
Many financial analysts across the world try to understand on a daily basis if the price of a specific stock will go up or down. They combine all the existent theory regarding valuation with their practical experience and insight as support to strengthen their arguments over the fair value they recommend/’sell’. Similarly, my objective in this dissertation was to present different valuation methodologies and achieve reliable and as accurate as possible the share fair value of Banco Comercial Português, also known as Millennium BCP. The year-end 2013 price target yielded by my valuation model was 0,157 Euros per share, representing a potential return to the investor of 65,2% - BUY recommendation. I also performed a sensitivity matrix, showing how the implicit price target changes due to small changes in key variables of the model. Furthermore, a comparison with an equity research of a leading investment bank was done, mainly focusing on methodologies followed and results obtained.